Time Course of Early Hematoma Expansion in Acute Spot-Sign Positive Intracerebral Hemorrhage: Prespecified Analysis of the SPOTLIGHT Randomized Clinical Trial. Issue 3 (9th February 2023) - Al-Ajlan, Fahad S.; Gladstone, David J.; Song, Dongbeom; Thorpe, Kevin E.; Swartz, Rick H.; Butcher, Kenneth S.; del Campo, Martin; Dowlatshahi, Dar; Gensicke, Henrik; Lee, Gloria Jooyoung; Flaherty, Matthew L.; Hill, Michael D.; et al.
Abstract : Background: In the SPOTLIGHT trial (Spot Sign Selection of Intracerebral Hemorrhage to Guide Hemostatic Therapy), patients with a computed tomography (CT) angiography spot-sign positive acute intracerebral hemorrhage were randomized to rFVIIa (recombinant activated factor VIIa; 80 μg/kg) or placebo within 6 hours of onset, aiming to limit hematoma expansion. Administration of rFVIIa did not significantly reduce hematoma expansion. In this prespecified analysis, we aimed to investigate the impact of delays from baseline imaging to study drug administration on hematoma expansion. Methods: Hematoma volumes were measured on the baseline CT, early post-dose CT, and 24 hours CT scans. Total hematoma volume (intracerebral hemorrhage+intraventricular hemorrhage) change between the 3 scans was calculated as an estimate of how much hematoma expansion occurred before and after studying drug administration. Results: Of the 50 patients included in the trial, 44 had an early post-dose CT scan. Median time (interquartile range) from onset to baseline CT was 1.4 hours (1.2–2.6). Median time from baseline CT to study drug was 62.5 (55–80) minutes, and from study drug to early post-dose CT was 19 (14.5–30) minutes. Median (interquartile range) total hematoma volume increased from baseline CT to early post-dose CT by 10.0 mL (−0.7 to 18.5) in the rFVIIa arm and 5.4 mL (1.8–8.3) in the placebo arm ( P =0.96). Median volume change between the early post-dose CT and follow-up scan was 0.6 mL (−2.6 to 8.3) in the rFVIIa arm and 0.7 mL (−1.6 to 2.1) in the placebo arm ( P =0.98). Total hematoma volume decreased between the early post-dose CT and 24-hour scan in 44.2% of cases (rFVIIa 38.9% and placebo 48%). The adjusted hematoma growth in volume immediately post dose for FVIIa was 0.998 times that of placebo ([95% CI, 0.71–1.43]; P =0.99). The hourly growth in FFVIIa was 0.998 times that for placebo ([95% CI, 0.994–1.003]; P =0.50; Table 3). Conclusions: In the SPOTLIGHT trial, the adjusted hematoma volume growth was not associated with Factor VIIa treatment. Most hematoma expansion occurred between the baseline CT and the early post-dose CT, limiting any potential treatment effect of hemostatic therapy. Future hemostatic trials must treat intracerebral hemorrhage patients earlier from onset, with minimal delay between baseline CT and drug administration. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01359202.